Role of decentralized clinical trials in cancer drug development: Results from a survey of oncologists and patients. (May 2022) - de las Heras, Begoña; Daehnke, Adam; Saini, Kamal S; Harris, Melissa; Morrison, Kenneth; Aguilo, Ariel; Chico, Isagani; Vidal, Laura; Marcus, Robin
As a result of the unprecedented challenges imposed by the COVID-19 pandemic on enrollment to cancer clinical trials, there has been an urgency to identify and incorporate new solutions to mitigate these difficulties. The concept of decentralized or hybrid clinical trials has rapidly gained currency, given that it aims to reduce patient burden, increase patient enrollment and retention, and preserve quality of life, while also increasing the efficiency of trial logistics. Therefore, the clinical trial environment is moving toward remote collection and assessment of data, transitioning from the classic site-centric model to one that is more patient-centric.